What Is the Subject Like? Critical and Clinical in the Poems of Oliverio Girondo - Vich, Víctor (2022)
This essay studies the representation of subjectivity in Oliverio Girondo’s poetry based on three types of figurations: the decentering of identity, the crisis of the will and the death drive. The analysis attempts to show, on the one hand, the importance that these representations had in a context that demanded unitary, coherent and productive subjects and, on the other hand, to locate the critique that this poetry addresses to modern reason. The essay lists the strategies elucidated to reconfigure subjectivity before the world, before language and before itself.